2021
DOI: 10.1128/msphere.01090-20
|View full text |Cite
|
Sign up to set email alerts
|

APEX2 Proximity Proteomics Resolves Flagellum Subdomains and Identifies Flagellum Tip-Specific Proteins in Trypanosoma brucei

Abstract: Trypanosoma brucei is the protozoan parasite responsible for sleeping sickness, a lethal vector-borne disease. T. brucei has a single flagellum (cilium) that plays critical roles in transmission and pathogenesis. An emerging concept is that the flagellum is organized into subdomains, each having specialized composition and function. The overall flagellum proteome has been well studied, but a critical knowledge gap is the protein composition of individual subdomains. We have tested whether APEX-based proximity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 90 publications
(208 reference statements)
2
19
0
Order By: Relevance
“…2c and Extended Data Fig. 2b) as expected from the presence of a transmembrane domain (TMD) and consistent with previous reports 17,18 . The probability of colocalization between two fluorescently tagged protein populations was determined by the coordinatebased colocalization (CBC) analysis method of Malkusch, et al 1) showed significant colocalization for CARP3-ACP1 (p < 0.05) that was in the same range as the positive control (CARP3-PAmCherry-CARP3mNG;…”
Section: Carp3 Is a Flagellar Tip Protein Essential For Social Motility And Colonization Of Tsetse Fly Salivary Glandssupporting
confidence: 91%
See 2 more Smart Citations
“…2c and Extended Data Fig. 2b) as expected from the presence of a transmembrane domain (TMD) and consistent with previous reports 17,18 . The probability of colocalization between two fluorescently tagged protein populations was determined by the coordinatebased colocalization (CBC) analysis method of Malkusch, et al 1) showed significant colocalization for CARP3-ACP1 (p < 0.05) that was in the same range as the positive control (CARP3-PAmCherry-CARP3mNG;…”
Section: Carp3 Is a Flagellar Tip Protein Essential For Social Motility And Colonization Of Tsetse Fly Salivary Glandssupporting
confidence: 91%
“…1e, Extended Data Fig. 1h), consistent with subcellular proteome studies 16,17,40 . CARP3 is concentrated at the tip of the parental and daughter flagella (Fig.…”
Section: Carp3 Is a Flagellar Tip Protein Essential For Social Motility And Colonization Of Tsetse Fly Salivary Glandssupporting
confidence: 82%
See 1 more Smart Citation
“…mNeonGreen and APEX2-tagged cell lines were generated in the 29-13 background by C-terminal tagging (40) with pPOTv6-puro-puro-mNG or pPOTv7-blast-blast-APEX2-3xHA, respectively. pPOTv7-blast-blast-APEX2-3xHA contains the same APEX2-3xHA tag as in (48). For MC3-NG, a transient CRISPR-Cas9 system (49) was used to tag both alleles.…”
Section: Methodsmentioning
confidence: 99%
“…Proximity-dependent biotinylation approaches have been extremely useful for studying the protein interactome of T. brucei in various contexts. These include the identification of bilobe components ( Morriswood et al., 2013 ); changes resulting from the ectopic expression of developmentally-regulated RNA-binding proteins ( De Pablos et al., 2017 ); mapping the interactome of the T. brucei cytokinetic machinery ( Hilton et al., 2018 ); identification of key proteins required for microtubule quartet anchorage to basal bodies ( Dong et al., 2020 ); novel cytoskeleton-associated proteins essential for morphogenesis and cytokinesis ( Schock et al., 2021 ); and flagellum tip-specific proteins ( Vélez-Ramírez et al., 2021 ). Still within the umbrella of fluorescence, TrypTag has been an invaluable tool for the parasitology community.…”
Section: Imagingmentioning
confidence: 99%